Characterization of interface defects in ALD Al2O3/p-GaSb MOS capacitors using admittance measurements in range from kHz to GHz. (April 2016) - Gu, Siyuan; Min, Jie; Taur, Yuan; Asbeck, Peter M.
Highlights: ALD Al2 O3 /p-GaSb MOS capacitors were measured using AC signal from kHz to GHz. The GHz technique is promising for high-k oxide and III–V interface characterization. The effect of bulk oxide traps via hole and electron tunneling was studied. We analyzed C–V & G–V frequency dispersion with interface and bulk-oxide trap modeling. Abstract: Atomic layer deposited (ALD) Al2 O3 /p-type GaSb Metal–Oxide–Semiconductor (MOS) capacitors are studied with capacitance–voltage (C–V) and conductance–voltage (G–V) measurements using AC signal frequencies covering the range from kHz to GHz. The potential and limitations of the measurements at GHz frequencies for oxide and interface defect characterization are described. The effect of bulk oxide traps in communication with the GaSb valence band via hole tunneling is highlighted. Modeling indicates that the C–V and G–V frequency dispersions observed in the accumulation, flat-band and depletion regions of the Al2 O3 /p-GaSb MOS capacitors are due to combined contributions of bulk-oxide traps and interface traps.